The Long-Run Evolution of Infrastructure Services - Hugh Goldsmith (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper traces the 11,000 year evolution of infrastructure systems during major periods of innovation, expansion and diffusion. Throughout history, the key role of the State is self-evident. Private sector involvement has waxed and waned over millennia, although at times it has been pivotal in bringing innovation, taking risks and driving efficiency. It is argued that positive feedback between early capital market development and investment in infrastructure innovations that lowered system-wide transaction costs has been a critical factor in sustaining growth since 1800. The paper sets out a model of infrastructure innovation cycles, stressing that only an evolutionary, multi-disciplinary, systems approach embracing technology, finance, and institutions can capture such long term, complex dynamics.
Keywords: H54; B52; O33; N70; 330; infrastructure; evolutionary economics; innovation